A meta-analysis of eight factors influencing MOOC-based learning outcomes across the world - Yu Z. (2023)
With the development of information technologies, many learners opt to stay home receiving various forms of online education such as massive open online courses (MOOC). However, many learners and instructors complain that MOOC-based learning effectiveness has been dampened by many factors. Through a meta-analysis using Stata/MP 14.0, this study reveals that MOOC-based learning outcomes can be significantly influenced by eight factors, i.e. behavior intention, learning engagement, students’ motivation, perceptions, satisfaction, performance, self-regulation, and social networks across the world. Future research could reveal more influencing factors pivoting on the forum improvements, as well as the effect of social presence on MOOC-based learning outcomes.